Periodontal Diseases as a Risk Factor for Severe Course and Mortality in COVID-19 – An Interdisciplinary Analysis in Light of Available Studies - Piotr Marcjasz; Anna Bioły; Agnieszka Borończyk; Piotr Zając; Agnieszka Buliszak; Monika Babczyńska (Quality in Sport)
Introduction: COVID-19 can progress to life-threatening illness in some patients, and identifying modifiable risk factors for severe outcomes is crucial. Periodontal diseases cause systemic inflammation and share risk factors with conditions linked to worse COVID-19 outcomes [7]. Recent studies worldwide have suggested that periodontitis may independently aggravate COVID-19 severity [5]. This interdisciplinary analysis aims to examine current evidence on whether periodontal disease is a risk factor for severe COVID-19 progression and mortality.